Genetic Polymorphism of NAT2 Gene and its Association with Prostate Cancer - Nesa, A; Rahman, MT; Kabir, Y; Rupam, FA (Anwer Khan Modern Medical College Journal, 2014)
A N acetyltransferases 2 (NAT2) is one of the phase II metabolizing enzyme that participate in the bioconversion of heterocyclic arylamines into electrophilic nitrenium ions, which are important ultimate carcinogens that are directly implicated in tumor initiation process. Prostate epithelial cell express N acetyltransferases (NAT) enzymes and recent molecular epidemiological studies have analyzed the relationship between NAT2 in etiology of prostate cancer. A review by chen (2001) in prostate cancer (PCa) suggests that the frequencies of some polymorphisms in certain genes differ among different racial and ethnic groups. In a case control study in India by Srivastava and Mittal (2005), observed significant association between rapid acetylator genotype NAT2 and PCa in tobacco users (OR = 3.43, 95% CI: 1.68-7.02, p< 0.001) when compared with controls. Hamasaki et al (2003) in Japanese men, observed the frequency of the NAT slow acetylator genotype was statistically higher among prostate cancer patients (17.1%) compared with controls (8.6%). Another case control study in Turkey by Kosova et al. (2009), concluded that Nat2* 6A and NAT2 *7A/B gene polymorphism were significantly associated with prostate cancer. DOI: http://dx.doi.org/10.3329/akmmcj.v5i2.21131 Anwer Khan Modern Medical College Journal Vol. 5, No. 2: July 2014, Pages 39-42